Influence of Understanding, Income and Environment of Muzakki on The Performance of Paying Zakat: Study on Colombo Market Traders - Bin Alisa, Muhammad Amirullah (Journal of Contemporary Applied Islamic Philanthropy, 2024)
Purpose: This study aims to test partial and simultaneous how understanding, income, and influence on the environment muzaki pay zakat. Methodology: In this study, the data used is primary data. The method used to collect data using questionnaires. Then, the data analysis techniques used in this research are to test the validity, reliability, and multiple regression analysis. Findings: The results of the study were processed with SPSS version 20.0 for Windows. Based on an analysis conducted by the author, there is a positive effect of variable understanding of the behavior of the variable pay zakat. It is seen from the results of multiple regression analysis of the coefficient of 0.364 and significance of (0.000) <0.05 and T arithmetic> T table (3.820> 1.251). while the variable income does not have a positive influence on the behavior of variable pay zakat. This can be seen from the results of multiple regression analysis of the coefficient of -0.046 and significance (0.541)> 0.05 and T count <T table (-0.617 <1.251). Similarly, with muzaki environment variables that do not provide a positive influence on the behavior of variable pay zakat. This can be seen from the results of multiple regression analysis and significance of 0.018 (0.830)> 0.05 and T count <T table (0.216 <1.251). From these results the most dominant factor influencing the behavior of paying zakat is variable understanding as a positive influence on the behavior of pay zakat and have a T count is greater than the other variables.